2018
DOI: 10.1177/0146167218769867
|View full text |Cite
|
Sign up to set email alerts
|

Are Liberals and Conservatives Equally Motivated to Feel Empathy Toward Others?

Abstract: Do liberals and conservatives differ in their empathy toward others? This question has been difficult to resolve due to methodological constraints and common use of ideologically biased targets. To more adequately address this question, we examined how much empathy liberals and conservatives want to feel, how much empathy they actually feel, and how willing they are to help others. We used targets that are equivalent in the degree to which liberals and conservatives identify with, by setting either liberals, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
175
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(200 citation statements)
references
References 60 publications
21
175
4
Order By: Relevance
“…Previous research suggests that self-identified conservatives are less motivated to feel empathy than liberals 15 . Consistent with these findings, we found that ESJ and EC were negatively correlated (r = −0.32, p < 0.001).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research suggests that self-identified conservatives are less motivated to feel empathy than liberals 15 . Consistent with these findings, we found that ESJ and EC were negatively correlated (r = −0.32, p < 0.001).…”
Section: Resultsmentioning
confidence: 94%
“…However, research cited in support of ideological palliation 12,13 does not clearly isolate the relationship between economic beliefs and responses to inequality. Ideological differences in affect might reflect not only the power of system-justifying economic beliefs to lessen inequality aversion but rather the influence of other factors associated with system-justifying ideologies-such as insensitivity to a broad range of macro-level threats 14 or low levels of motivation to feel empathy 15 . By experimentally manipulating the salience of economic inequality and accounting for the effects of general empathy, the studies reported here allow us to focus on the link between system-justifying beliefs and reactions to inequality.…”
mentioning
confidence: 99%
“…We are not arguing that social dominants deliberately employ motivated cognition strategies to feel certain emotions that can best justify their actions and beliefs, although this might be the case. For example, both liberals and conservatives actually want to feel less empathy for out-group members(Hasson et al, 2018), suggesting that there could be a motivational component to our phenomenon.…”
mentioning
confidence: 93%
“…There is evidence for both formulations. For example, liberals and conservatives report feeling less empathy for political out-group in general, without referencing a particular target or event (Hasson et al, 2018). This suggests that individuals might be predisposed to feel reduced empathy towards out-group targets in general.…”
mentioning
confidence: 99%
“…This is because people with egalitarian values are often those who are driven by the desire to eliminate inequality, and to ensure that people are treated fairly and equitably (cf. Hasson, Tamir, Brahms, Cohrs, & Halperin, ). A high‐status privilege in aiding people who have encountered a misfortune potentially widens rather than closes the compassion gap between the advantaged and the disadvantaged.…”
Section: The Value‐orientation Thesismentioning
confidence: 99%